Molecular characterization of yerba mate chlorosis-associated virus, a putative cytorhabdvirus infecting yerba mate (Ilex paraguariensis) - Bejerman, Nicolas Esteban; De Breuil, Soledad; Debat, Humberto Julio; Miretti, Marcos; Badaracco, Alejandra; Nome Docampo, Claudia (2017)
We present the molecular characterization of a new virus infecting yerba mate (Ilex paraguariensis St. Hil.) in Argentina. Deep sequencing of diseased yerba mate plants showing chlorotic linear patterns, chlorotic rings, and vein yellowing resulted in the identification of a new virus resembling plant rhabdoviruses in sequence and genome structure. We have determined the complete genome sequence of this virus, which is 12,876 nt long. Seven open reading frames (ORFs) were identified in the antigenomic orientation of the negative-sense, single-stranded viral RNA, in the order 3′-N-P-P3-P4-M-G-L-5′. Phylogenetic analysis suggested that the described virus is a new member of the genus Cytorhabdovirus, which was supported by the observation of rhabdovirus-like particles within the cytoplasm of infected yerba mate cells. The virus has been tentatively named “yerba mate chlorosis-associated virus” (YmCaV). The availability of the YmCaV genome sequence will contribute to assessing the genetic variability of this virus and determining its role in this yerba mate disease.